Solitary Plasmacytoma of the Breast: A Case of an Uncommon Breast Neoplasm - McCormack, Sean; Hamad, Eyad; Hamad, Amar (Case Reports in Hematology, 2023)
Plasmacytoma is a rare cancer that originates from a single plasma cell and is characterized by the abnormal proliferation of monoclonal plasma cells. It is typically localized in a single area of the body, most commonly in the bone or soft tissue. Solitary plasmacytoma can be further classified as either solitary plasmacytoma of bone (SPB) or solitary extramedullary plasmacytoma (SEP or EMP). Diagnosis may be delayed in symptomatically silent plasmacytomas, but early diagnosis and prompt treatment are crucial for the management of this disease. The mean age for patients with plasmacytoma varies depending on the specific type of plasmacytoma, but generally, it is more common in older adults. Soft tissue plasmacytomas are uncommon, and plasmacytomas manifesting within the breast are extremely rare, especially when they are not a manifestation of multiple myeloma (MM). This report presents a case of SEP of the breast in a 79-year-old female patient. This rare disease needs to be studied further in terms of long-term survival and disease progression to MM. By raising awareness and understanding of plasmacytoma, we aim to improve outcomes and quality of life for patients affected by this disease.